Studi Efisiensi Sistem Reduction Gear pada Pembangkit Listrik Tenaga Gas - Said Aiyub; M. Ghufran Habibi; Fauzi Fauzi (Jurnal Teknologi, 2022)
Gas power plants produce electrical energy by a generator driven by a gas turbine through a rotational transmission device called a Reduction Gear. Reduction gear consists of two rotating gears tangent to each other with different diameter sizes. This difference in diameter size makes the output side shaft of the reduction gear, which has a larger diameter, rotate slower than the input side shaft of the reduction gear which has a smaller diameter of the gear. Analysis of the performance of the reduction gear device is done by calculating its efficiency. In this study, the total power loss is 459.18 kW where the gear power loss (Pvz) is 112.53 kW, the bearing power loss (Pvz0) is 342.24 kW, and the power loss due to seals (Pvs) of 4.41 kW. With an input power of 33,000 kW, the efficiency of this reduction gear is 98.61%.